INFECTION CONTROL PRACTICES IN HEALTHCARE SETTINGS: REVIEWING BEST PRACTICES FOR PREVENTING HEALTHCARE-ASSOCIATED INFECTIONS, INCLUDING HAND HYGIENE, PERSONAL PROTECTIVE EQUIPMENT (PPE) USE, AND ENVIRONMENTAL CLEANING. - Sultan HamadBin Ali Al Fadhil, Abdulhadi Hassan Hamad Alsallum, Mohamad Hassan Hamad Laslom, Mohammed Jakhair F Mal Rezg, Mohammed Rashed Mohammed Al Dhawi, Mubarak Hussain ahmadAlqadrah, Marzoog Saleh Al Salaiea, Maiedh Saleh BureakALsalaim; Abdullah Nasser M Al Sallum (Chelonian Research Foundation, 2023)
This article comprehensively audits the best ways to prevent healthcare-associated infections (HAIs) in healthcare settings, centering on methodologies such as hand cleanliness, individual defensive gear (PPE), and natural assurance. Synthesizing existing information gives a comprehensive diagram of the adequacy of these measures in decreasing HAIs and progressing persistent security. The survey highlights the significance of using contamination control methods and chief hand cleanliness in avoiding transmission and reducing the HAI hazard. Moreover, it highlights the effect of utilizing individual defensive hardware to diminish the spread of irresistible infections. It emphasizes the significance of great natural cleanliness to decrease the microbial spread of illnesses. By joining an evidence-based point of view, this survey gives imperative direction to clinicians and approach producers in executing infection control methodologies, which is advantageous to ensure persistent well-being and diminish the burden of nosocomial contaminations within the hospital. Keywords Infection control, Healthcare-associated infections (HAIs), Hand hygiene, Personal protective equipment (PPE), Environmental cleaning, Healthcare settings, Patient safety.